Scenario-Based Model for the Location of Multiple Uncapacitated Facilities: Case Study in an Agro-Food Supply Chain (2021)
Supply chains for agricultural products have taken on great importance in recent times due to the need that exists for consumers to acquire fresh products in excellent quality conditions. In the design of supply networks for this type of product, the location of facilities and allocation decisions are among the most relevant decisions in operations management, which in many cases involve aspects of uncertainty. This research proposes to plan the distribution of multiple agro-food products taking into account the location and capacities of producers, potential location of facilities and variations in crop yields. A scenario-based optimization model for the location of multiple uncapacitated facilities is developed. The model is tested in the cassava agro-food chain in Sucre, Colombia. First, the description for the construction of the scenarios for the uncertainty associated with the yield per hectare of cassava crops is presented. Next, the mixed integer programming model (MIP) for the location of uncapacitated facilities (UFLP) is presented. The aim of the model is to minimize operational distribution costs. The results of the case study were obtained with the help of the CPLEX Solver integrated in GAMS in low computational time. A reduction of costs by almost 60% of the distribution costs is obtained.